Dinamika Pembuktian Dan Penjatuhan Hukum Dalam Kasus Kekerasan Seksual Anak - Apsari, Raditya Dihyan; Zuhda Mila Fitriana (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
Sexual violence against children is classified as an extraordinary crime because, in addition to violating the law, it also destroys human values. Children as victims are in a very vulnerable position, both physically and psychologically, so the criminal justice system must provide maximum protection through a fair trial and sentencing process. This study examines Decision No. 254/Pid.Sus/2023/PN Mks, in which the panel of judges acquitted the defendant in a case of sexual violence against children. The aim is to assess the extent to which the system of evidence and the judges' considerations reflect the principles of substantive justice and victim protection. Using a legal-normative method and a descriptive-analytical approach, the results of the study show that the evidence in this case is still formalistic, relying on conventional evidence and ignoring the psychological vulnerability of the victim. In fact, Law No. 12 of 2022 on Sexual Violence Crimes emphasises that the victim's testimony accompanied by psychological evidence can stand as valid evidence. These findings confirm the need to reformulate the approach to evidence and punishment so that law enforcement officials do not only focus on legalistic aspects but also guarantee the restoration of victims' rights and protection for vulnerable groups.